Feline GM1 gangliosidosis: characterization of the residual liver acid beta-galactosidase. - Holmes, E W (1978)
The residual liver acid beta-galactosidase (beta-gal) activity from a case of feline GM1 gangliosidosis was partially purified and characterized with respect to its pH optimum, kinetic properties, thermostability, isoelectric point, molecular weight, and antigenicity. In comparison to the normal enzyme, the mutant enzyme had the same pH optima for the three substrates tested, a reduced Km for 4-methylumbelliferyl-beta-gal, elevated Km's for GM1 and asialofetuin (ASF), and increased thermolability. In addition, the mutant beta-gal had a higher isoelectric point, a reduced molecular weight, and appeared to be antigenically different from normal. The results suggest that the mutation in the Birmingham GM1 cat is structural and that the residual enzyme activity is a structurally altered acid beta-gal. The apparent lack of antigenic identity between the mutant and normal enzymes, in contrast to the situation in many human GM1 patients, is most unusual.